Mathematical modeling of interactions of cabergoline with human serum albumin for biosensing of human serum albumin - Jalalvand, Ali R. (2019)
In this work, we are going to study the interactions of cabergoline (CBG) with human serum albumin (HSA) by mathematical modeling of voltammetric and spectroscopic data. To achieve this goal, voltammetric and spectroscopic data will be augmented into a data matrix which will be resolved by multivariate curve resolution-alternating least squares (MCR-ALS) as a powerful chemometric tool. Then, the quality of the data fitting by MCR-ALS will be examined by MCR-BANDS to ensure about the absence of the rotational ambiguities in the results. Molecular docking will also be used to model the interactions of CBG with HSA for verifying the results obtained from experimental methods. Hard-modeling of the experimental data will be performed by EQUISPEC to compute the binding constant of the complex formed from the interactions of CBG with HSA for verifying the binding constant obtained by direct analysis of the experimental data. Finally, two chrono-amperometric measurements based on CBG-HSA interactions will be performed to develop a novel electroanalytical method for determination of electro-inactive HSA.